(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Low vision significantly impacts daily activities in urban areas like Lahore, Pakistan. Understanding the prevalence and underlying causes of low vision is crucial for developing effective health policies, enhancing service accessibility, and strengthening low-vision rehabilitation efforts. Objective(s): To assess the frequency and leading cause of low vision in Lahore. Methodology: This four-month observational cross-sectional study was started at the University of Lahore Teaching Hospital (ULTH) and LRBT, involving 140 patients aged 10 to 60 years diagnosed with low vision. Using a non-probability convenient sampling method, the study ensured ethical compliance by obtaining informed consent and maintaining participant confidentiality. Data collection included comprehensive eye exams (e.g., visual acuity, refraction, slit-lamp, fundoscopy, tonometry, and visual field testing), structured questionnaires, and medical record reviews to assess demographics, medical history, and the impact of low vision on quotidian life. Data was securely recorded and analyzed using SPSS version 27, with descriptive statistics to identify common causes of low vision. Results: Of the total 140 participants, 71 were female (50.7%) and 69 were male (49.3%). In terms of age, the prime group was those aged 51–60 years (56 participants, 40.0%), followed by the 41–50 year group (29 participants, 20.7%). Among the causes of low vision, Retinitis Pigmentosa was the most common, affecting 33 participants (23.6%), followed by Glaucoma (18 cases, 12.9%) and Cataract (15 cases, 10.7%). ARMD (Age-Related Macular Degeneration) and Diabetic Retinopathy accounted for 11 (7.9%) and 10 (7.1%) cases, respectively. Other notable causes included Myopia (8.6%), Macular Dystrophy (6.4%), Maculopathy (5.7%), Nystagmus (4.3%), Corneal Opacity (3.6%), and Optic Atrophy, which was the least common, affecting only 4 participants (2.9%) and other diseases also include, retinal detachment, macular scar and PVD. Conclusion(s): This study concluded that retinal disorders, particularly Retinitis Pigmentosa and Glaucoma, are the leading contributors to low vision in this population, with a clear trend of increased prevalence among individuals over 50 years of age.